Study on Temperature Rise and Deformation of Radial Double-face Mechanical Seal End Faces of the Ultra-high-speed Drive System - Zhao Tianqi; Yi Jinbao; Wen Menggang; Xiao Yanbin; Shi Xiaofeng; Pan Yang (Jixie chuandong)
The operating speed of the radial double-end mechanical seal of the lubricating oil in the ultra-high-speed gear transmission bearing chamber of the torpedo turbine engine is as high as 50 000 r/min. Facing extreme conditions such as friction heat generation, high temperature and high pressure of the sealing medium, the sealing performance is difficult to guarantee, thus affecting the lubrication characteristics of gears and bearings. To solve this problem, the thermal-fluid-solid coupling simulation model of the mechanical seal of the ultra-high speed gearbox was established, and the cooling water flow field of the mechanical seal and the temperature rise and deformation of its end face were analyzed. The effects of spring pressure, cooling water flow and static ring interference on the temperature rise and deformation of the seal end face under hot conditions were studied. The results show that the pressure difference between the two sides of the inner seal in the hot state is 1.1 MPa, which is 11 times that of the cold state. The maximum temperature of the inner and outer seal faces reaches 400 ℃ and 370 ℃, which is about three times that in the cold state. The deformation of the seal end face in the hot state is greater than that in the cold state, and the deformation of the inner seal end face is greater than that of the outer layer. The temperature rise of the seal end face increases with the increase of the spring pressure and decreases with the increase of the cooling water flow rate. The optimal cooling water flow rate is 0.2 kg/s. With the increase of spring pressure, the deformation of the end face of the moving ring gradually increases, while the deformation of the end face of the static ring is almost unchanged, and the cooling water flow rate has little effect on the deformation of the sealing end face. The deformation of the end face in the static ring increases with the increase of the interference, and the deformation of the end face of the inner static ring is larger than that of the outer layer.